Measuring User Experience Using Cognitive Walkthrough in the JKN Mobile Applicatio - Apsari, Ayudyah Eka; Aminuddin, Rezki Amelia (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 10 No 01 (2024): Volume 10 No 01 Tahun 2024, 2024)
The JKN mobile application is an application owned by BPJS Kesehatan, through this application participants can get primary and tertiary health services. Based on a preliminary study of 30 BPJS Kesehatan participants in Makassar City, it is known that 37% of users do not know about the JKN mobile application, 33% of users prefer to come directly to the nearest BPJS Kesehatan service office and 30% of users have difficulty using the JKN mobile application. The lack of participants using the JKN mobile application has an impact on the tight queues for services at the BPJS Kesehatan office and at health facilities. Thus, this study aims to test the reusability of the JKN mobile application by using a cognitive walkthrough and an analysis of the level of user experience using the User Experience Questionnaire (UEQ). Measurement of usability with cognitive walkthrough showed that the average respondent completed all tasks in 312.4 seconds. The success rate of completing the task was achieved 100% by 40% of respondents and the task that was completed correctly by the respondent was 29%. The measurement of user experience with UEQ is 1.26 based on the positive impression given by the JKN mobile application after being used by respondents. The different test results were obtained from the non-parametric statistical t test, which showed that there was no difference in the usability assessment and the JKN mobile user experience. The overall user experience is above average, so there is still a need to improve the JKN mobile interface.